Forensic examination of Castor seeds (Ricin): Analytical method develop ment using ALS microscopy, Planar Chromatography and UV-spectroscopy (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Ricin, a highly toxic protein found in castor bean seeds, is a potential agent for biological  warfare and a major concern for national authorities worldwide. The assassination  of Georgi Markov using ricin highlighted the forensic importance of detecting this  poison. The present study aims to develop an analytical method, to facilitate detection  and forensic analysis of ricin. The study employs visual characterization to examine  the physical features of the seeds, and thin-layer chromatography (TLC), and UV visible spectrometry for chemical examination to confirm the presence of ricin. The  research design involves conducting solvent extraction and TLC, followed by optical  characterization by the use of UV-Vis spectrometry, for quick and unambiguous  identification of ricin for forensic purposes. This study reports, for the first time,  extensive morphological analysis of castor seeds, green solvent extraction and  optimization of TLC. By developing an easy and effective method for the examination  of castor seeds and ricin, this study provides a reliable additional test for detecting  ricin in castor seeds, which is crucial for forensic and security purposes.
Keywords: Ricin; Castor seeds; Forensic examination; Microscopy of castor seeds; Thin layer chromatography (TLC); UV-visible spectrometry of Castor